2023
DOI: 10.1177/20552076231173227
|View full text |Cite
|
Sign up to set email alerts
|

The usability testing of the integrated electronic healthcare services for diabetes mellitus patients during the pandemic in Indonesia

Abstract: Introduction Diabetes mellitus is a degenerative disease that obliges patients to take continuous healthcare services. During a pandemic situation, all access to healthcare facilities becomes limited. A web-based integrated electronic-healthcare system (IeHS) study was used to overcome this problem. This study aimed to describe patients’ ability to access and understand this web-based application. Method An observational study using a web-based IeHS took place in Muara Tebo, Indonesia, in 2021. A total of 82 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…These results showed that the application could be used for all age groups irrespective of educational background, familiarity with smartphone operation, and internet accessibility level [ 77 ]. However, certain studies reported inconsistent results on the association between sociodemographic factors and perceived usability among the general population and pharmacists, respectively [ 77 – 79 ]. Significant associations were previously shown between demographic-related variables and usability [ 80 ] from an investigation conducted among participants with years of mobile application experience [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that the application could be used for all age groups irrespective of educational background, familiarity with smartphone operation, and internet accessibility level [ 77 ]. However, certain studies reported inconsistent results on the association between sociodemographic factors and perceived usability among the general population and pharmacists, respectively [ 77 – 79 ]. Significant associations were previously shown between demographic-related variables and usability [ 80 ] from an investigation conducted among participants with years of mobile application experience [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between all numerical and categorical variables will be analyzed using the T-test (parametric) or Mann-Whitney (non-parametric). To determine the data distribution, normality analysis will be done using Kolmogorov Smirnov (data more than 50) [15,16]. A value of p<0.05 indicated that there was a relationship between the two variables.…”
Section: Discussionmentioning
confidence: 99%
“…The descriptive analysis of education level in this study is in line with previous research which found that people with low education suffer more from diabetes mellitus as 83.8%. 16 Education is important in understanding management, blood sugar control, addressing symptoms that arise, and preventing complications. Patients with higher education have better knowledge about diabetes and its effects on health, so they can respond to the disease positively and will try to handle it.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with higher education have better knowledge about diabetes and its effects on health, so they can respond to the disease positively and will try to handle it. 16 From the research results at the Lubuk Kilangan Health Center, the number of patients with type 2 diabetes mellitus based on work was dominated by patients who did not work, including homemakers and retirees. The descriptive analysis of the type of work in this study is in line with research conducted by Muliyani 23 The type of work can affect physical activity and stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation